(untitled) (Research, Society and Development, 2022)
Current society’s masculinity incorporates historical and cultural processes, which are transgerational. Expressions used on a daily basis such as “real men don’t get sick”, “real men don’t feel pain”, “seeking medical advice is women’s thing” are widespread in the popular rhetoric and reflect social demands that consider autonomy, strength, risk-seeking behaviors, and emotional control as part of the male essence. The goal of this study is to understand the social and cultural construction of being a southern Brazilian man (gaucho) according to the perspective of Pierre Bourdieu. It consists of a qualitative, interpretative study analyzed through the concepts of male domination of Pierre Bourdieu performed with nine men undergoing treatment for prostate cancer. Data collection was performed through a semi-structured interview, and thematic analysis was used for data analysis. An Ethics Committee approved this research project (under number 2.608.801). According to our results, being a man involves a social construction of superiority in comparison with women. Being a man was related to physical strength and providing money to the house. This vision of superiority is usually a social construction passed through generations. In this perspective, these demonstrations of superiority, courage, nobility would be expected from the real man. Therefore, we can conclude that social conceptions of male dominance influence the way which men live, as their psychosocial identity is marked by values, behaviors and attitudes that are socially constructed.